2001
DOI: 10.1159/000057570
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenesis and Neuronal Regeneration in the Adult Reptilian Brain

Abstract: Evidence accumulated over the last few decades demonstrates that all reptiles examined thus far continue to add neurons at a high rate and in many regions of the adult brain. This so-called adult neurogenesis has been described in the olfactory bulbs, rostral forebrain, all cortical areas, anterior dorsal ventricular ridge, septum, striatum, nucleus sphericus, and cerebellum. The rate of neuronal production varies greatly among these brain areas. Moreover, striking differences in the rate and distribution of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
159
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(172 citation statements)
references
References 115 publications
(145 reference statements)
9
159
0
4
Order By: Relevance
“…The formation of new neurons in reptiles is strongly regulated through proliferation within the ventricular zone. The number of dividing cells is photoperiod-dependent, (4) but the molecular mechanisms involved remain unknown. In fishes, a cell-extrinsic cue that may drive adult neurogenesis, is the neuropeptide somatostatin.…”
Section: Cell-intrinsic Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of new neurons in reptiles is strongly regulated through proliferation within the ventricular zone. The number of dividing cells is photoperiod-dependent, (4) but the molecular mechanisms involved remain unknown. In fishes, a cell-extrinsic cue that may drive adult neurogenesis, is the neuropeptide somatostatin.…”
Section: Cell-intrinsic Mechanismsmentioning
confidence: 99%
“…However, the brain territories undergoing adult neurogenesis follow patterns that vary between species and may relate to different functions. (4)(5)(6) Here we review current knowledge of some widely used model systems (see also Fig. 1), although more extensive comparative work is clearly needed to assess the general value of these observations for each taxonomic group.…”
Section: Introductionmentioning
confidence: 99%
“…The present study showed that in reptiles, at least in lizards, lateral ventricular system is responsible for massive proliferative activity. The specialized ependyma known as sulci are exclusively possessed by reptiles, they are remnants of the embryonic germinative tissue and still retain their proliferative potential till adulthood (Font et al 2001). It has been reported that recognized sulcus septomedialis was similar to the neurogenic centers and responsible for adult neurogenesis in birds (Alvarez-Buylla et al 1990).…”
Section: Adult Neurogenesis In Non-mammalian Vertebratementioning
confidence: 99%
“…We hypothesize that these differences depend on the coordinated interaction between different environmental cues and growth of sensory systems. It is conceivable that corresponding sensory brain regions are closely associated with local adult neurogenesis (Alvarez-Buylla et al 1990;Polenov & Chetverukhin 1993;Zupanc 1999;Font et al 2001;Hou & Wu 2007).…”
Section: Adult Neurogenesis In Non-mammalian Vertebratementioning
confidence: 99%
“…There is some evidence that telomere biology is different in turtles (Girondot and Garcia, 1999), and some results suggest that the brains of turtles have enhanced mechanisms to protect against reactive oxygen species formation and damage (Lutz et al, 2003). Likewise, neurogenesis may be predominant in reptiles (Font et al, 2001). Since other turtles may feature negligible senescence and oocyte regeneration (Finch, 1990), turtles are promising models for antiaging medicine (de Magalhaes, 2004).…”
Section: Potential Nonmammalian Models Of Antiaging Strategiesmentioning
confidence: 99%